Growth hormone therapy in patients with Noonan syndrome - Go Hun Seo; Han-Wook Yoo (Korean Society of Pediatric Endocrinology, 2018)
Noonan syndrome (NS) is an autosomal dominant disorder that involves multiple organ systems, with short stature as the most common presentation (>70%). Possible mechanisms of short stature in NS include growth hormone (GH) deficiency, neurosecretory dysfunction, and GH resistance. Accordingly, GH therapy has been carried out for NS patients over the last three decades, and multiple studies have reported acceleration of growth velocity (GV) and increase of height standard deviation score (SDS) in both prepubertal and pubertal NS patients upon GH therapy. One year of GH therapy resulted in almost doubling of GV compared with baseline; afterwards, the increase in GV gradually decreased in the following years, showing that the effect of GH therapy wanes over time. After four years of GH therapy, ~70% of NS patients reached normal height considering their age and sex. Early initiation, long duration of GH therapy, and higher height SDS at the onset of puberty were associated with improved final height, whereas gender, dosage of GH, and the clinical severity did not show significant association with final height. Studies have reported no significant adverse events of GH therapy regarding progression of hypertrophic cardiomyopathy, alteration of metabolism, and tumor development. Therefore, GH therapy is effective for improving height and GV of NS patients; nevertheless, concerns on possible malignancy remains, which necessitates continuous monitoring of NS patients receiving GH therapy.